SUGARCANE AGRIBUSINESS PARTNERSHIP AND FOOD SECURITY: THE ROLE OF WONOLANGAN SUGAR FACTORY IN POLICY IMPLEMENTATION IN DRINGU VILLAGE, PROBOLINGGO REGENCY - Fitrianti, Deistiara; Marwiyah, Siti; Maksin, Mastina (Jurnal PUBLIQUE, 2026)
Food security requires cross-sectoral engagement, including the role of industry in strengthening commodity-based agribusiness systems. This study aims to analyze the role of Wonolangan Sugar Factory in supporting the implementation of food security policy through partnerships with sugarcane farmers in Dringu Village, Probolinggo Regency. A qualitative approach with a descriptive design was employed, utilizing in-depth interviews, observation, and documentation as data collection techniques. Informants were selected purposively, including factory management, sugarcane farmers, and other relevant stakeholders. Data were analyzed using an interactive model involving data reduction, data display, and interpretation. The findings reveal that Wonolangan Sugar Factory plays a strategic role as a non-state actor in local food security policy implementation through the provision of production inputs, technical assistance, and guaranteed purchase of harvest outputs. The partnership generates both economic and institutional benefits for farmers while ensuring a stable supply of raw materials for the industry. This practice reflects a collaborative interaction between industry and farmers that contributes to strengthening the local food system. At the same time, several constraints remain evident, including limited farmer resources, price volatility, weak coordination among stakeholders, and external pressures such as climate variability and infrastructure limitations. These challenges indicate the need for strengthening partnership governance through capacity building, transparency in cooperation mechanisms, and more integrated institutional arrangements. This study contributes to the literature on collaborative policy implementation and provides empirical insights into the role of industrial actors in local food security systems.